Assessment of the Classification of the Northwestern Dialect of the Mari Language from the Perspective of Glottochronology - Julia V. Normanskaja (Финно-угорский мир, 2024)
Introduction. The classification of the Northwest dialect of the Mari language is currently not entirely clear. According to the Encyclopedia of the Mari El Republic, the “Northwest Mari language exhibits some features of both Hill Mari and Meadow-Eastern Mari languages.” However, G. Bereсzki believed that the Northwest dialect belongs to the Hill Mari language. The aim of the study is to analyze the linguistic similarity assessment of the language of the first Gospel created by Priest S. Bobrovsky (1821) and the dialect of the 20th century according to the data of I. G. Ivanov and G. M. Tuzharov, in relation to the Hill and Meadow Mari languages from the perspective of glottochronology.